An analysis of Zambia's emergency medicine registrars' experience in South Africa : lessons for the development of emergency medicine care in Zambia - Mwanza, Kephas Elimon (Stellenbosch : Stellenbosch University, 2019)
Thesis (MMed)--Stellenbosch University, 2019.